Translation Equivalence in Horror Movie - Ni Gusti Ayu Putu Agustin Ariantini; Made Susini; Dewa Ayu Kadek Claria (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2026)
This study aims to analyze how subtitling in Pamali: The Corpse Village preserves elements of fear and cultural meaning through various types of equivalence and pragmatic strategies. Using Baker’s theory of equivalence, this research explores how subtitling influences the audience's experience of horror films. The research employs a descriptive qualitative analysis method. The data consist of dialogues taken from a film that have been translated into English, which are then categorized based on the types of equivalence used in the subtitling. Additionally, this study identifies pragmatic strategies in translating dialogues that contribute to conveying fear to the audience. The findings reveal that seven types of equivalence from Baker are applied in the film’s subtitling. They include Equivalence at Word Level, Equivalence above Word Level, Grammatical Equivalence, Textual Equivalence: Thematic and Information Structure, Textual Equivalence: Cohesion, Pragmatic Equivalence, and Beyond Equivalence. In transferring the source meaning, subtitling through these seven types of equivalence can successfully transfer the core message. In preserving elements of fear and cultural meaning, in some cases, subtitling may lead to some consequences. Subtitling through Equivalence at Word Level may slightly diminish the cultural and horror element inherent in the SL text caused by the occurence of non-equivalence words in the SL texts.  Equivalence above Word Level when working on the translation of idiom by paraphrasing, Grammatical Equivalence focusing on grammatical Person, and Pragmatic Equivalence may also lose the cultural meaning of the SL texts. Textual Equivalence achieved through the change of thematic structure may reduce the element of fear of the movie.